2015
DOI: 10.1186/s12862-015-0327-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of lysine acetylation in the RNA polymerase II C-terminal domain

Abstract: BackgroundRPB1, the largest subunit of RNA polymerase II, contains a highly modifiable C-terminal domain (CTD) that consists of variations of a consensus heptad repeat sequence (Y1S2P3T4S5P6S7). The consensus CTD repeat motif and tandem organization represent the ancestral state of eukaryotic RPB1, but across eukaryotes CTDs show considerable diversity in repeat organization and sequence content. These differences may reflect lineage-specific CTD functions mediated by protein interactions. Mammalian CTDs conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…The number and complexity of these non-consensus heptads roughly correlate with developmental complexity 3 . Expression of genes involved in multicellularity were affected by mutating non-consensus heptads of mouse cells in culture 4 , despite data indicating that the non-consensus heptads are not essential for the viability of human cells grown in culture 5 . Likewise, deletion of a small region encompassing several non-consensus heptads caused severe developmental defects and growth retardation in mice 6 , demonstrating that non-consensus heptads may contribute to development and cellular differentiation.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The number and complexity of these non-consensus heptads roughly correlate with developmental complexity 3 . Expression of genes involved in multicellularity were affected by mutating non-consensus heptads of mouse cells in culture 4 , despite data indicating that the non-consensus heptads are not essential for the viability of human cells grown in culture 5 . Likewise, deletion of a small region encompassing several non-consensus heptads caused severe developmental defects and growth retardation in mice 6 , demonstrating that non-consensus heptads may contribute to development and cellular differentiation.…”
mentioning
confidence: 83%
“…The diversity of CTD sequences across eukaryotes has been recently acknowledged 3 , though the functional significance of many non-consensus heptads has not been widely investigated. Non-consensus CTD repeats may expand the repertoire of available PTMs, thus increasing the complexity of signalling through the CTD 4,[35][36][37][38] . In our minimal system, we observed that non-consensus motifs that contained conservative deviations from the consensus responded similarly to Dm P-TEFb and Ssu72.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lysine residues at position 7 of eight heptad repeats are acetylated by the acetyltransferase p300/CBP (KAT3A/B) (K7ac), and are also mono-and di-methylated by an asyet-unknown methyltransferase (Dias et al, 2015;Schroder et al, 2013;Voss et al, 2015;Weinert et al, 2018). These lysine residues evolved in higher eukaryotes in the common ancestor of the metazoan lineage, and are highly conserved among vertebrates (Simonti et al, 2015). While lysine-7 mono-and di-methylation marks are found near promoters, K7ac is enriched in gene bodies (Dias et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, K7ac marks are found at ~80% of actively transcribed genes, with a peak in signal +500 bp downstream of the transcription start site (TSS), indicating that the modification could more broadly regulate the transition from transcription initiation to productive elongation (Schroder et al, 2013). In a genetic model in which all eight K7 residues were mutated to arginines (8KR), cells expressing 8KR RPB1 exhibited altered expression of genes relating to development, multicellularity and cell adhesion, underscoring a critical role of K7ac in the development of higher eukaryotes (Simonti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%